PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI WILAYAH HUKUM POLRES SUKABUMI (STUDI KASUS PEMBOBOLAN ALFAMART) - Fransiskus, Dedy; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
A comprehensive government policy towards non-crime is implemented using government institutions, government regulations and laws with the aim of upholding societal norms including legal regulations as control and public reconciliation. This research aims to answer how to enforce the law. Criminal acts of theft with weights in the Sukabumi Police jurisdiction and studied the obstacles and challenges with a case study of theft with the weight of a mini market burglary specialist, this type of research carried out empirically. The data used in this research comes from primary data and secondary data. Secondary data consists of primary legal materials, secondary legal materials and tertiary legal materials. Data collection methods using literature study and interviews. Meanwhile, data analysis uses qualitative descriptive methods. Based on the results of the research, it was concluded: Law enforcement of criminal acts of theft with weighting in the jurisdiction of the Sukabumi Police, case study of the Alfamart Burglary Police Report Number: LP/ B /11 / I / 2024/ SPKT/ POLRES SUKABUMI / POLDA JAVA BARAT, January 10 2024, The crime of theft is applied with weights and the need for alternative prevention that needs to be carried out in collaboration with the community in accordance with the provisions of Article 15 paragraph (1), especially letter c, to minimize crime in the Sukabumi Police jurisdiction